2020
DOI: 10.1007/s12282-020-01151-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of germline TP53 variants among early-onset breast cancer patients from Polish population

Abstract: Background The objective of this study was to determine spectrum and prevalence of germline mutations in TP53 gene among Polish women with early-onset breast cancer (BC), which has not been determined until now. Methods A cohort of 100 females with BC diagnosed ≤ 30 years of age and with a positive family history of cancer was used as a discovery cohort. 1880 women with BC ≤ 45 years old and a control group of 2000 healthy women were genotyped as a replication phase of this study. Results Four heterozygous pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
1
3
0
Order By: Relevance
“…8,24,25 To date, the reported prevalence of TP53 and PALB2 germline mutations in Asian patients with familial and/or earlyonset breast cancers ranges from 0.4% to 6% 26-29 and 0.3% to 2.6%, 21,26,[30][31][32][33][34] respectively. They are almost similar to the reported prevalence of TP53 and PALB2 germline mutations in familial and/or early-onset breast cancer patients in the Western countries which ranges from 4% to 6.4% 35,36 and 0.1% to 2.9%, [37][38][39][40] respectively. Notably, the majority of studies in the Western populations have been carried out on selected BRCA1/2 negative familial and/or early-onset breast cancer patients.…”
Section: Introductionsupporting
confidence: 87%
“…8,24,25 To date, the reported prevalence of TP53 and PALB2 germline mutations in Asian patients with familial and/or earlyonset breast cancers ranges from 0.4% to 6% 26-29 and 0.3% to 2.6%, 21,26,[30][31][32][33][34] respectively. They are almost similar to the reported prevalence of TP53 and PALB2 germline mutations in familial and/or early-onset breast cancer patients in the Western countries which ranges from 4% to 6.4% 35,36 and 0.1% to 2.9%, [37][38][39][40] respectively. Notably, the majority of studies in the Western populations have been carried out on selected BRCA1/2 negative familial and/or early-onset breast cancer patients.…”
Section: Introductionsupporting
confidence: 87%
“…The second TP53 mutation (c.733G> A ) is also described for the first time in the Tunisian population. It is segregated in multiple families with LFS or LFS-like syndrome [ 28 , 29 ]. Clinicopathological characters of this mutation carrier showed an emerging phenotype of a classic LFS-breast cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients who are found not to carry a founder mutation, we perform full sequencing using gene panels including BRCA1, BRCA2, CHEK2, and PALB2 in breast cancer cases with familial clustering of this cancer and/or in patients with early onset disease (diagnosed at age 45 or below). In addition, we offer TP53 sequencing for women with breast cancer diagnosed at the age of 30 or below, as it was reported that about 5% of these women carry a TP53 mutation, and radiotherapy is contraindicated for TP53 mutation positive cases [59]. Such a sequential testing approach could be also used in other homogeneous groups, i.e., Ashkenazi Jewish, Icelandic individuals, and French-Canadians, in which the range of mutations is limited [60].…”
Section: Discussionmentioning
confidence: 99%